The Grand Manan Terrane of New Brunswick: Tectonostratigraphy and Relationship to the Gondwanan Margin of the Iapetus Ocean - Fyffe, Leslie R. (Geoscience Canada, 2014)
Recently gathered stratigraphic and U–Pb geochronological data indicate that the pre-Triassic rocks of the Grand Manan Terrane on the eastern side of Grand Manan Island can be divided into: (1) Middle Neoproterozoic (late Cryogenian) quartzose and carbonate sedimentary sequences (The Thoroughfare and Kent Island formations); (2) a Late Neoproterozoic (early Ediacaran) volcanic-arc sequence (Ingalls Head Formation); and (3) Late Neoproterozioc (mid- Ediacaran) to earliest Cambrian (early Terreneuvian) sedimentary and volcanic-arc sequences (Great Duck Island, Flagg Cove, Ross Island, North Head, Priest Cove, and Long Pond Bay formations). A comparison to Precambrian terranes on the New Brunswick mainland (Brookville and New River terranes) and in adjacent Maine (Islesboro Terrane) suggests that the sedimentary and volcanic sequences of the Grand Manan Terrane were deposited on the continental margin of a Precambrian ocean basin that opened during the breakup of Rodinia in the Middle Neoproterozoic (Cryogenian) and closed by the Early Cambrian (Terreneuvian) with the final assembling of Gondwana. Rifting associated with the initial opening of the Paleozoic Iapetus Ocean began in the Late Neoproterozoic (late Ediacaran) and so overlapped in time with the closing of the Precambrian Gondwanan ocean. The southeastern margin of the Iapetus Ocean is defined by thick sequences of quartz-rich Cambrian sediments (within the St. Croix and Miramichi terranes of New Brunswick) that were largely derived from recycling of Precambrian passive-margin sedimentary rocks preserved in the Grand Manan and Brookville terranes of New Brunswick and in the Islesboro Terrane of Maine. These Precambrian terranes are interpreted to represent dextrally displaced basement remnants of the Gondwanan continental margin of Iapetus, consistent with the model of a two-sided Appalachian system proposed by Hank Williams in 1964 based on his work in Newfoundland.